"Dingklik Oglak Aglik" Traditional Games Integration in Science Teaching Module to Promote Global Diversity - Primaharani, S.; Widiyawati, Y.; Sari, D. S. (Journal of Science Education Research, 2024)
Teaching modules can help students effectively participate in learning and achieve successful learning outcomes through the merdeka curriculum. Developing games that are appropriate to science learning, one of which is traditional games. This research aims to test the feasibility of an integrated teaching module for the traditional game dingklik oglak aglik to promote global diversity so that it is suitable for use in schools at the junior high school. This research method is quantitative descriptive research. The data collection instrument used is an instrument for assessing the quality of teaching modules which is seen from 3 criteria, namely didactic, construction, and technical. The research results of the science teaching module integrated with the traditional game dingklik oglak aglik to promote global diversity showed very high validity reaching 94%. Teachers consider this teaching module to be very practical and suitable for use. Therefore, it can be concluded that the science teaching module integrated with the traditional game dingklik oglak aglik to promote global diversity has a high level of validity and practicality so this teaching module is suitable for usability.